Semiconductor surfaces structurization induced by ultrasound - Savkina, R.K. (Functional Materials, 2012)
Gallium arsenide and silicon substrates were exposed to cavitation impact induced by focusing a high frequency acoustic wave into liquid nitrogen. Optical and atomic force microscopy methods as well as energy dispersive X-ray spectroscopy were used for analysis of the surface morphology and chemical composition of semiconductor surface. Microstructures formation as well as change of the chemical composition of the surface was found. The morphology of the structures is highly dependent on the acoustic parameters.